Blocking the means and its applications in the Maliki school (Comprehensive Journal of Science, 2026)
This study discusses the principle of blocking the means in Islamic law. It is a principle that aims to prevent actions that may lead to prohibited acts, in order to achieve the goals of Sharia in bringing benefit and preventing harm. The study confirms that Islamic law is comprehensive and valid for all times and places, and that all human actions fall under the five legal rulings.The study also explains that the principle of blocking the means is connected to the outcomes of actions, where means are judged according to what they lead to; if they lead to something unlawful, they take its ruling. The importance of this principle appears in protecting the five essentials: religion, life, intellect, wealth, and honor, which are the basis of social stability.The study presents evidence for this principle from the Qur’an, the Sunnah, and the statements of the Companions and Successors, with focus on the Maliki school’s use of it as a source of legal reasoning, while emphasizing that it is not limited to the Maliki school.It also explains the research methodology, which includes textual, inductive, descriptive, deductive, and inferential approaches, and outlines the research plan covering the definition of the principle, its evidence, its rules, and its applications in Islamic jurisprudence.
Keywords: Blocking the means, the Maliki school, objectives of Islamic law, Islamic legal rulings, the five necessities